Marine Natural Products Against Tuberculosis - Marcus Vinícius Nora De Souza (The Scientific World Journal)
Natural products represent an outstanding source of compounds that play an important role in the treatment of human diseases. Due to the importance of nature as a source of new drug candidates, the aim of this review is to highlight the marine natural products, which exhibit antituberculosis activity, discovered between 2000 and 2005.